2021
DOI: 10.22541/au.162730423.33094139/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of early postoperative period results of patients with type 2 diabetes taking oral anti-diabetics or insulin medications, with microalbuminuria and normal creatinine levels after coronary artery bypass.

Abstract: Introduction: In this study, we aimed to compare the early postoperative period results of type 2 diabetes patients taking oral antidiabetics or insulin medications, with microalbuminuria and normal creatinine levels after coronary artery bypass. Materials and methods: Eighty patients with type 2 diabetes and taking oral antidiabetics or receiving insulin medication all with normal creatinine levels with microalbuminuria were included in this study. Preoperative creatinine values of the patients, albumin level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…Yu (2016) [22] 50 50 28/22 27/23 10:5 ± 0:9 10:6 ± 1:1 (1), ( 2), ( 3), ( 4), ( 5), (6) 3.3.2. Effect of Nursing Intervention on 2hPG.…”
Section: Effect Of Nursing Intervention On Fbgmentioning
confidence: 99%
See 1 more Smart Citation
“…Yu (2016) [22] 50 50 28/22 27/23 10:5 ± 0:9 10:6 ± 1:1 (1), ( 2), ( 3), ( 4), ( 5), (6) 3.3.2. Effect of Nursing Intervention on 2hPG.…”
Section: Effect Of Nursing Intervention On Fbgmentioning
confidence: 99%
“…In 2015, it was reported that 415 million people aged 20-79 have diabetes, which is expected to reach 642 million by 2040 [3,4]. Globally, the number of diabetes patients has quadrupled in the past few years, and 90% of diabetes patients are type 2 diabetes [5], which is mainly caused by insulin resistance due to various reasons [6]. Due to the change of dietary structure and the reduction of physical activity, obese children are gradually increasing, and the number of children and adolescents with type 2 diabetes is raising year after year [7], although type 1 diabetes is mostly in children.…”
Section: Introductionmentioning
confidence: 99%